(untitled) (Bangladesh Medical Journal, 2016)
For more than a century, blood transfusion is recognized as an important contributor to patients outcome. This study was focused on frequent indications of reported blood transfusions. This cross-sectional type of descriptive study was conducted in Faridpur, Bangladesh among the 719 patients from April, 2013 to July 2013. 30% had non-hemorrhagic anemia, 21% had intra or post-partum hemorrhage, 7% were undergoing haemodialysis, 6% had thalassemia, 4% had trauma, 2% had non-hematological cancer, 1% had leukemia and the rest had other causes. Middle age group and female patients required more transfusions. Moreover, conservative managements required more blood transfusion rather than surgical. However, Patients receiving a blood transfusion are at risk of increased morbidity, mortality, length of stay in hospital & ICU. Bangladesh Med J. 2016 May; 45 (2): 85-89